PENINGKATAN HASIL BELAJAR MATA KULIAH KORESPONDENSI BAHASA INGGRIS MELALUI PENDEKATAN GENRE - Bambang Suratman, ; Syafi&rsquo (Pendidikan Ekonomi, 2009)
Poor English language competence and ineffective approach employed so far resulted in unsatisfactory learning achievement. The teacher researcher, therefore, carried out a classroom action research aimed at improving students learning result. The research was intended to find out the students learning result in the English correspondence course by using genre based approach and their response to the approach. This study employed classroom action research procedure consisting of planning, action, observation, and reflection. The 2006- year students of office administration comprising 25 students served as the subject of the study. The study stipulates that 84 % and 88% of the students achieved minimum score threshold in the second and third cycle respectively. Moreover, most of the students had positive response to the application of genre based approach to the course.